PERANAN 'MORNING BRIEFING' TERHADAP MOTIVASI BELAJAR DAN INSPIRASI BAGI MAHASISWA TEKNIK ELEKTRO POLITEKNIK ENJINERING INDORAMA : TELAAH HASIL JAWABAN PADA KUESIONER - Occe Luciana (Universitas Nasional, 2018)
Motivation and inspiration are two words that cannot be separated from student success. By this motivation, students will try to learn hard to achieve the achievement while students who are inspired by something they heard, seen, or felt, will usually be motivated to do creative things. This is very important for students as agent of change in the world of education. The motivation and inspiration for students can be obtained through the morning briefing activities; the information sharing activities from lecturers to students. This study is what the author did at Politeknik Enjinering Indorama as one of campuses that carried out the morning briefing. The results showed that the morning briefing had an influence on student learning motivation, as evidenced by the chi-square test found no value because the motivation variable showed the same value, not different at all. All respondents in assessing the motivation questionnaire showed the value of AGREE all. The results of statistical analysis show that the morning briefing does not inspire students. This is shown by Asymp. Sig. (2-sided > 0.05, it can be concluded that the morning briefing variable is not related to inspiration. Morning briefings conducted at the Electrical Engineering has an influence on learning motivation, students agree with the morning briefing because it can motivate their learning, but not for the inspiration variable. Morning briefing cannot inspire students of Electrical Engineering students.morning briefing